Coloniality and meritocracy in unequal EU migrations : intersecting inequalities in post-2008 Italian migration - Varriale, Simone (Book collections on Project MUSE., 2023)
Connecting decolonial theory with Bourdieu's class analysis, this book provides pioneering new insights into the social stratification of EU migrants and the relationships between neoliberalism, coloniality and European whiteness.